2023
DOI: 10.25165/j.ijabe.20231603.7711
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of sow estrus using a lightweight real-time detector and thermal images

Haibo Zheng,
Hang Zhang,
Shuang Song
et al.

Abstract: Determination of ovulation time is one of the most important tasks in sow reproduction management. Temperature variation in the vulva of the sows can be used as a predictor of ovulation time. However, the skin temperatures of sows in existing studies are obtained manually from infrared thermal images, posing an obstacle to the automatic prediction of ovulation time. In this study, an improved YOLO-V5s detector based on feature fusion and dilated convolution (FD-YOLOV5s) was proposed for the automatic extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Jeong et al [92] measured average rectal and vulvar skin temperature and found a non-significant difference (38.8 • C for in-estrus sows vs. 38.7 • C for non-estrus sows). Zheng et al [9] used an infrared thermal imaging technique guided by YOLOV5s detector to monitor and detect sow estrus in real-time. The model detected estrus with 89.3% sensitivity, 94.5% specificity and 5.8% error rate.…”
Section: Infrared Thermography In Estrus Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeong et al [92] measured average rectal and vulvar skin temperature and found a non-significant difference (38.8 • C for in-estrus sows vs. 38.7 • C for non-estrus sows). Zheng et al [9] used an infrared thermal imaging technique guided by YOLOV5s detector to monitor and detect sow estrus in real-time. The model detected estrus with 89.3% sensitivity, 94.5% specificity and 5.8% error rate.…”
Section: Infrared Thermography In Estrus Detectionmentioning
confidence: 99%
“…There are great provisions to introduce technological tools in the PLF system. Out of many branches of PLF, breeding pigs in healthy, depression-free conditions and noncontact forms has always been the target worldwide [6,7] as accurate and timely reproduction is essential to the swine business [8][9][10][11][12]. According to several studies, proper detection of estrus in sows plays a crucial role in predicting the correct insemination time and gaining desired production generation after generations [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Distinguished from the aforementioned methods, the present method employs environmental parameters to counterbalance the temperature losses from environmental disturbances and accurately segments the incomplete thermal window region. Reference [35] introduced a method to extract the vulva region of sows, based on the improved YOLOv5s object detection algorithm [35]. In comparison, the method proposed herein can precisely delineate the sow vulva boundary, accommodate variations of sow vulva across different sizes, and enhance the accuracy and reliability of thermal infrared temperature measurement.…”
Section: Comparison Of Different Prediction Algorithmsmentioning
confidence: 99%